(untitled) (Salud, Arte y Cuidado, 2022)
As a guiding purpose, this research seeks to interpret the ethics of the university academic manager as a transversal axis in citizen training and from the specific, it tries to understand the meaning that they have about ethics, the ethical principles exercised by the work on campus; of the values ​​that determine its action and the role in the formation of the citizen that it is in charge of educating. In addition, from the development of its epistemological and philosophical foundations in the emerging paradigm, epistemologically, the research was oriented under the qualitative paradigm, with the support of a hermeneutical phenomenological approach. When interpreting the ethics in the university manager we will be able to leave written, on what he lives explicitly and implicitly on a daily basis, while exercising his actions. Taking into consideration that the profession with which he works, prepares the highest percentage of professionals; and there is not, perhaps, a single professional who has not passed through the hands of one of them. In short, the approach to the research topic proposes a reform for managers in the institutional context of higher education, a new paradigm reflective educational, critical that confronts the dismantling of some social utopias, tolerance in all fields, uncertain politics, inequality, social injustice, the power of social manipulation, and the deterioration of values.Principio del formulario